Pola Semiotika Representasi Emosi pada Desain Sampul Buku Anak: Analisis Peirce pada The Feelings Series Karya Trace Moroney - Hestia Rachmat Nunciata Lubis; Yosef Yulius; Bobby Halim (JURNAL RUPA, 2025)
The study investigates semiotic patterns of emotional representation in children’s book cover design using Charles Sanders Peirce’s icon-index-symbol framework. The research examines ten book covers from The Feelings Series by Trace Moroney, a children’s picture book series that consistently addresses basic emotions in early childhood. The study aims to identify how emotional meanings are constructed through visual signs and to examine the dominant semiotic strategies employed across covers. A descriptive qualitative method was employed was applied through structured visual observation of key cover elements, including character facial expressions, body gestures, color palettes, typography, and background composition. Each visual element was treated as a unit of analysis and independently coded by two coders according to Peirce’s classification of iconic, indexical, and symbolic signs. Inter-coder reliability was assessed using percentage agreement, resulting in an initial agreement rate of 90%, with remaining discrepancies resolved through reflective discussion grounded in operational definitions and contextual visual analysis. The findings reveal a consistent cross-cover semiotic pattern in which indexical signs such as body posture, gesture, gaze direction, and compositional emphasis play a dominant role in constructing emotional context, while iconic signs, particularly facial expressions, function as primary cues for immediate emotional recognition. Symbolic signs, including color conventions, typographic treatment, and series identity, operate to stabilize and reinforce emotional meanings through culturally familiar visual codes. These three sign types work in an integrated manner to form a cohesive and readable system of emotional representation across the series. The study demonstrates that Peirce’s semiotic framework can be systematically operationalized as and analytical tool in visual communication design research, particularly within the context of children’s emotional literacy. The identified semiotic patterns provide practical insights for designers and publishers in developing children’s book cover that effectively communicate emotions in ways that are visually clear, developmentally appropriate, and emotionally supportive.